Inovasi Eco-Enzyme dalam Mendukung Pemerintah Menuju Net Zero Emission di Indonesia - Fadhil Wahyu Yulistiar; Singgih Manggalou (Public Inspiration : Jurnal Administrasi Publik, 2023)
To support the Indonesian government's efforts in achieving the Net Zero Emission target, one reliable solution is to apply the Eco-Enzyme innovation. Eco-Enzyme is an environmentally friendly alternative solution in waste management, especially at the community level as the smallest line. By using Eco-Enzyme, organic waste can be broken down into simpler elements, making it easier and more efficient to process. Additionally, the use of Eco-Enzyme can also help reduce greenhouse gas emissions generated from waste incineration. From this, it can be concluded that the implementation of the Eco-Enzyme innovation in waste management has a positive impact on the environment and supports the government's efforts to achieve the Net Zero Emission target in Indonesia.